Geomorphic approach of controlling mass movements on Tama Koshi road in Central Nepal - M.R. Dhital (Lowland Technology International, 2017)
The heavy monsoonal precipitation of 2012 in central Nepal triggered off or reactivated many mass movements on the Tama Koshi road. A site survey of unstable grounds was carried out to recommend short- and long-term control measures. The landslide control works were recommended mainly on the basis of detailed geomorphic mapping supplemented with some geotechnical investigation of soils, and most of these structures are working satisfactorily.